1967
DOI: 10.1136/gut.8.5.482
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteins in ulcerative colitis: electrophoretic patterns in the inferior mesenteric artery and vein.

Abstract: EDITORIAL COMMENT. These studies suggest that there is a local production or release of alpha 2 globulins and a fixation or destruction of gamma globulin by the diseased colon.Previous studies have indicated that in patients with severe attacks of ulcerative colitis, changes occur in the levels of the serum proteins. These changes consist principally of a fall in the serum albumin level, and a rise in the level of the alpha 2 globulins (Bicks, Kirsner, and Palmer, 1959;Brooke, Dykes, and Walker 1961;Soergel an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1968
1968
1973
1973

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…However, recent studies in our own department have confirmed Broberger and Perlmann's findings in vivo, and they indicate that immune gamma globulin is fixed in the colon in the living colitis patients (de Dombal, 1967).…”
Section: Psychological Factorssupporting
confidence: 73%
“…However, recent studies in our own department have confirmed Broberger and Perlmann's findings in vivo, and they indicate that immune gamma globulin is fixed in the colon in the living colitis patients (de Dombal, 1967).…”
Section: Psychological Factorssupporting
confidence: 73%
“…When at admission to hospital during an acute attack the patient's y-globulin levels were raised, and/or rising, remission occurred. However, when the level of y-globulins was low and falling, the patient invariably had to proceed to surgery (de Dombal, 1967b). These findings powerfully support the view that y-globulins can play a defensive role.…”
Section: Serological Evidencementioning
confidence: 58%
“…Outpatients in remission who were free from infectious and incidental diseases such as influenza and bronchitis were chosen for study. Fifteen patients with levels of a2-globulin above the normal range suffered an acute attack within three months, while 35 patients with normal or diminished a2-globulin levels suffered no such attacks (de Dombal, 1967b). When at admission to hospital during an acute attack the patient's y-globulin levels were raised, and/or rising, remission occurred.…”
Section: Serological Evidencementioning
confidence: 98%
See 1 more Smart Citation
“…But this argument was in part refuted by their further studies (Perlmann & Broberger, 1963) showing that the leucocytes from patients with ulcerative colitis had a cytotoxic effect upon the foetal colon cells in tissue culture, an effect which was inhibited by pre-treatment with colon antigen. Broberger & Perlmann's pioneer work has recently been confirmed and extended (Fink, Donnelly & Jablokow, 1967;Watson, Quigley & Bolt, 1966;de Dombal, 1967).…”
Section: Psychological Factorsmentioning
confidence: 84%